Advances in Quantum Computing: Bridging Theoretical Models ‎and Practical Applications - Goyal, Shobhit; Deepak , Shashikant; Das , Dr. Manoranjan; Aranganathan, Dr. A.; Kumar , M. Sunil; Bhatnagar , Tarang; Grover, Madhur (International Journal of Basic and Applied Sciences, 2025)
Notwithstanding the academic and engineering obstacles encountered in the advancement of Quantum Computers (QC), significant strides ‎are being made to advance the integration of the method to commercial uses. This article examines the solutions several companies are ‎developing with quantum hardware. The research presents these as combinatorial challenges, demonstrating their use across four industry ‎sectors: cybersecurity, nanomaterials and medications, financial services and banking, and modern manufacturing. Although QC is not now ‎available at the requisite scale to address all combinatorial issues, the research delineates three imminent prospects arising from ‎advancements in QC: quantum-safe cryptography, material and medicine exploration, and quantum-inspired methods‎.